2015
DOI: 10.1038/npp.2015.341
|View full text |Cite
|
Sign up to set email alerts
|

Selective Mitochondrial Targeting Exerts Anxiolytic Effects In Vivo

Abstract: Current treatment strategies for anxiety disorders are predominantly symptom-based. However, a third of anxiety patients remain unresponsive to anxiolytics highlighting the need for more effective, mechanism-based therapeutic approaches. We have previously compared high vs low anxiety mice and identified changes in mitochondrial pathways, including oxidative phosphorylation and oxidative stress. In this work, we show that selective pharmacological targeting of these mitochondrial pathways exerts anxiolytic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 49 publications
(48 reference statements)
0
28
0
2
Order By: Relevance
“…A previous study reported an association between oxidative stress and certain anxiety disorders (obsessive‐compulsive disorder and PD), implicating that oxidative metabolism may affect anxiety (Kuloglu et al, ). Furthermore, reduced ascorbic acid levels in the hippocampus of mice with high anxiety‐related behavior has been associated with anxiolytic effects of MitoQ treatment (Nussbaumer et al, ). Thus, ascorbic acid levels may reflect anxiety‐related changes in the periphery and the brain.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported an association between oxidative stress and certain anxiety disorders (obsessive‐compulsive disorder and PD), implicating that oxidative metabolism may affect anxiety (Kuloglu et al, ). Furthermore, reduced ascorbic acid levels in the hippocampus of mice with high anxiety‐related behavior has been associated with anxiolytic effects of MitoQ treatment (Nussbaumer et al, ). Thus, ascorbic acid levels may reflect anxiety‐related changes in the periphery and the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo metabolic labeling with a 15 N‐labeled diet introduces the stable nitrogen isotope 15 N into amino acids of live organisms. We have previously used in vivo 15 N metabolic labeling to identify protein expression changes in mouse models of neuropsychiatric phenotypes and investigated the effects of pharmacologically manipulating these changes . Here, we show that in addition to protein expression, 15 N metabolic labeling can simultaneously yield protein turnover data, information that cannot be gained by immunochemical methods.…”
mentioning
confidence: 87%
“…of pharmacologically manipulating these changes [10]. Here, we show that in addition to protein expression, 15 N metabolic labeling can simultaneously yield protein turnover data, information that cannot be gained by immunochemical methods.…”
mentioning
confidence: 89%
“…In Tierstudien und in-vitro werden bereits Substanzen zur Behandlung von psychiatrischen Erkrankungen durch pharmakologische Beeinflussung der Atmungskette erprobt [25][26][27]. Im Mausmodell konnten anxiolytische Effekte nach Gabe eines mitochondrienspezifischen Antioxidans erzielt werden [28].…”
Section: Somatische Untersuchungenunclassified
“…Es gibt einige Hinweise aus randomisiert-kontrollierten Studien auf Basis derer der Einsatz von antioxidativen Substanzen sowie Creatin und Coenzym Q10 empfohlen werden kann [38,39]. Weitere mitochondrienspezifische Antioxidantien werden erst im Tiermodell erprobt [28,40].…”
Section: Somatische Untersuchungenunclassified